On the occurrence of equatorial F‐region irregularities during solar minimum using radio occultation measurements. Issue 2 (26th February 2013) - Carter, B. A.; Zhang, K.; Norman, R.; Kumar, V. V.; Kumar, Sushil
Abstract: [1] The technique of radio occultation (RO) is demonstrated to be a powerful tool for studying equatorial F‐region irregularities (EFIs) associated with equatorial plasma bubbles. The extensive 4.9 year RO dataset of the Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC) satellites was employed in this study and contains EFI observations under a wide variety of solar and geomagnetic conditions. From an analysis of the EFI occurrence dependence on season/longitude, it is found that the EFI occurrence statistics largely match those reported previously, with the exception of an equinoctial EFI occurrence maximum in the American sector that is absent from previous studies. It is revealed that this maximum is due to enhanced EFI occurrence near the South Atlantic anomaly, where EFIs are expected to be suppressed by particle precipitation. An investigation into the solar activity dependence of the EFI occurrence characteristics revealed significant increases in the range of local times and latitudes with solar activity for most longitude sectors and seasons. Finally, the EFI suppression and enhancement effects of storm‐time electric fields are also investigated using the COSMIC data. Key Points: COSMIC RO data provides a long‐term global perspective of EFI occurrence COSMIC RO EFI occurrence characteristics agree well with previous studies EFI occurrence reveals a strong dependence on solar and geomagnetic activities